2000
DOI: 10.1073/pnas.160181697
|View full text |Cite
|
Sign up to set email alerts
|

Htra2-β 1 stimulates an exonic splicing enhancer and can restore full-length SMN expression to survival motor neuron 2 ( SMN2 )

Abstract: Spinal muscular atrophy (SMA), a common motor neuron disease in humans, results from loss of functional survival motor neuron (SMN1) alleles. A nearly identical copy of the gene, SMN2, fails to provide protection from SMA because of a single translationally silent nucleotide difference in exon 7. This likely disrupts an exonic splicing enhancer and causes exon 7 skipping, leading to abundant production of a shorter isoform, SMN2⌬7. The truncated transcript encodes a less stable protein with reduced self-oligom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
254
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 292 publications
(265 citation statements)
references
References 47 publications
10
254
0
1
Order By: Relevance
“…Htra␤1 increased approximately two-fold the levels of luciferase activity from the SMN2-luciferase construct without changing the levels of activity from the SMN1-luciferase construct, suggesting that hTra2␤1 specifically affects SMN exon 7 splicing rather than nonspecifically increasing expression levels (panel a). 21 RT-PCR from parallel transfections confirmed these results (Figure 3b). Other SR proteins previously reported to be incapable of stimulating full-length SMN expression from SMN2 also had no effect upon exon 7 splicing of SMN1 or SMN2 GFP and luciferase mini-gene constructs (data not shown).…”
Section: Transfection Of Mini-genes Into Mammalian Cellssupporting
confidence: 68%
See 2 more Smart Citations
“…Htra␤1 increased approximately two-fold the levels of luciferase activity from the SMN2-luciferase construct without changing the levels of activity from the SMN1-luciferase construct, suggesting that hTra2␤1 specifically affects SMN exon 7 splicing rather than nonspecifically increasing expression levels (panel a). 21 RT-PCR from parallel transfections confirmed these results (Figure 3b). Other SR proteins previously reported to be incapable of stimulating full-length SMN expression from SMN2 also had no effect upon exon 7 splicing of SMN1 or SMN2 GFP and luciferase mini-gene constructs (data not shown).…”
Section: Transfection Of Mini-genes Into Mammalian Cellssupporting
confidence: 68%
“…We have reported that Tra2␤1 stimulated exon 7 inclusion within SMN2 mRNA. 21 To identify factors and their potential roles in exon 7 splicing, we treated our stable cell lines with chemical compounds that stimulate or antagonize kinases and signaling pathways (Table 1). We tested the stress/MAP kinase pathway as it has been shown recently that p38 kinase/pathway played a role in alternative splicing of adenovirus E1A pre-mRNA by effecting the distribution and phosphorylation of hnRNP A1 protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tra2β specifically binds to the splicing enhancer within exon 7 of SMN1 pre-mRNA and facilitates inclusion of exon 7 in the mature SMN1 mRNA in neuroblastoma cell lines. 11 Similarly, Tra2β as well as SRSF1 (also known as ASF/SF2) and SRSF9 (SRp30c) promote inclusion of exon 10 of tau pre-mRNA. 12,13 Tra2β also facilitates alternative splicing of the CD44 gene via binding to CD44 exons v4 and v5, which is associated with breast cancer progression.…”
mentioning
confidence: 99%
“…SMA and AMCN are caused in a wide number of cases by a gene named SMN. Several exon or gene duplications and deletions or point mutations of this gene have been recorded associated to arthrogryposis [8,11,23]. SMN protein plays the key role of shuttle in distributing, regenerating and assembling the spliceosome complex [2,12].…”
Section: Introductionmentioning
confidence: 99%